Limits of carrier mobility in Sb-doped SnO2 conducting films deposited by reactive sputtering - B. Bissig; T. Jäger; L. Ding; A. N. Tiwari; Y. E. Romanyuk (APL Materials, 2015)
Electron transport in Sb-doped SnO2 (ATO) films is studied to unveil the limited carrier mobility observed in sputtered films as compared to other deposition methods. Transparent and conductive ATO layers are deposited from metallic tin targets alloyed with antimony in oxygen atmosphere optimized for reactive sputtering. The carrier mobility decreases from 24 cm2 V−1 s−1 to 6 cm2 V−1 s−1 when increasing the doping level from 0 to 7 at. %, and the lowest resistivity of 1.8 × 10−3 Ω cm corresponding to the mobility of 12 cm2 V−1 s−1 which is obtained for the 3 at. % Sb-doped ATO. Temperature-dependent Hall effect measurements and near-infrared reflectance measurements reveal that the carrier mobility in sputtered ATO is limited by ingrain scattering. In contrast, the mobility of unintentionally doped SnO2 films is determined mostly by the grain boundary scattering. Both limitations should arise from the sputtering process itself, which suffers from the high-energy-ion bombardment and yields polycrystalline films with small grain size.